Diagnostics of the Enterprise Economic Security and the Role of Information and Communication in the Context of Sustainability of Dynamical Equilibrium, Operation and Development - Skrynkovskyy Ruslan M.; Maksymchuk Iaroslava S.; Kharuk Kateryna B. (Problemi Ekonomiki, 2015)
In the scientific article a system for diagnostics of the enterprise economic security is developed. It has been determined that the main business indicators for diagnostics of the enterprise economic security are: the level of the enterprise financial stability (contains the indicator for the enterprise provision with its own funds, rate of independence, financial stability indicator, current assets to equity ratio, liquid ratio, absolute liquidity ratio, current liquidity ratio); level of the enterprise production activity (calculated on the output-capital ratio, capital-labor ratio, index of workforce productivity, quality indicators of fixed assets, production potential indicator, production profitability ratio, input-output coefficient); level of organizational and administrative activities of the enterprise (takes into account the ratio of administrative expenses to the rate of increase in production volume, rate of saving of the managerial apparatus, rate of information processing); level of employee loyalty to the enterprise (calculated on the rate of personnel turnover, rate of personnel continuity, indicator of employee satisfaction, personnel development indicator, education level of employees); level of scientific and technical and innovative activity of the enterprise (including index of profitability of innovations, profitability of expenditures on research and development works); level of investment activity of the enterprise (includes index of investment profitability, rate of investment activity, rate of return on investments, rate of investment in production); level of market reliability (calculated on index of return on sales, index of return on net assets, index of marketability, level of market research). It has been identified that an important role in the context of sustainability of dynamical equilibrium, operation and development of enterprises is played by information and communication.